Awareness and Use of Family Planning Methods among Married Women in A Community - Awal, Asmita; Chand, Ambika (Historical Journal, 2024)
Family planning/contraception reduces the need for abortion, especially unsafe abortion, reduces infant mortality, helps prevent HIV/AIDs, reduces adolescent pregnancies and helps to slow down increasing population growth. Over 60% of unintended pregnancies end in abortion, safe or unsafe, legal or illegal. An estimated 45% of all abortions remain unsafe and hospitalizes about 7 million women a year in developing countries. A descriptive cross-sectional research was carried out in ward no.14, Kathmandu Metropolitan city. The objective of this study was to find out awareness and use of Family planning method among married women in a community. Non probability, purposive sampling method was used. Sample size was 68 married women. The respondents mean age was 33.1 years and standard deviation was 6.5 years. All of the respondents (100%) were familiar with condom, pills, depo-provera, female sterilization whereas 95.6% heard about implants. Almost all of the respondents (98.5%) stated implants prevents pregnancy for 5 years and half of them (47.1%) were aware implants doesn't interfere with breast feeding. major source of information regarding family planning methods was from health professionals (80.8%) Whereas husband (13.2) level of awareness regarding family planning methods where 1.5% of the respondents had inadequate awareness, 54.3% had moderately adequate awareness and 44.1% of the respondents had adequate awareness. there is no significant association with age (0.479), duration of marriage (0.325), occupation (0.146) of the mother with level of awareness regarding family planning methods.